The impact of attributional style and homework experiences in Cognitive Behaviour Therapy for depression : a longitudinal investigation employing multilevel analysis : a dissertation presented in partial fulfillment of the requirements of the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Sachsenweger, Mieke (Massey University, 2010)
This longitudinal study aimed to investigate the moderating effects of attributional style on the relationship between homework experiences and depression severity throughout the course of therapy. Through an overarching depression study at Massey University, 28 participants experiencing first-episode Major Depressive Disorder (MDD) were recruited for 20 sessions of Cognitive Behaviour Therapy (CBT) plus follow-up sessions at two months. Clients were seen by seven doctoral students, and depression severity was monitored with the Beck Depression Inventory II (BDI-II) at each session, while attributional style was measured at six time points with the Attributional Style Questionnaire (ASQ). Homework was measured with the Homework Rating Scale II (HRS-II) at each session by clients, therapists and independent observers. A three-factor structure of the HRS-II was confirmed with the current data: 'benefits and completion'; 'costs and completion' and client 'beliefs'. Following preliminary analyses, benefits of homework completion was retained as the focus in a multilevel analysis investigation which utilised sessions up to the two month follow up. Therapist competence in assigning homework, and client depression severity, gender, and age were controlled for. No overall effect was found for homework in relation to depression over the course of therapy, and therefore attributional style did not moderate this relationship. However there was a trend towards a relationship between quantity and quality of homework and depression, which was moderated by a pessimistic attributional style. No effect was found for homework in relation to attributional style independently of depression severity. Attributional style on its own was related to depression severity over the course of therapy, as predicted. Women were significantly more depressed and less optimistic at intake than men, and older age correlated with lower pessimism and depression levels. Implications for future research and clinical practice are discussed.
Keywords: Cognitive Behaviour Therapy; Depression; Attributional style; Attribution; Homework; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology